Combined quantum-mechanics/molecular-mechanics dynamics simulation of A-DNA double strands irradiated by ultra-low-energy carbon ions - Ngaojampa C. (2017)
In order to promote understanding of the fundamentals of ultra-low-energy ion interaction with DNA, molecular dynamics simulations using combined quantum-mechanics/molecular-mechanics of poly-AT and poly-GC A-DNA double strands irradiated by < 200 eV carbon ions were performed to investigate the molecular implications of mutation bias. The simulations were focused on the responses of the DNA backbones and nitrogenous bases to irradiation. Analyses of the root mean square displacements of the backbones and non-hydrogen atoms of base rings of the simulated DNA structure after irradiation revealed a potential preference of DNA double strand separation, dependent on the irradiating energy. The results show that for the backbones, the large difference in the displacement between poly-GC and poly-AT in the initial time period could be the reason for the backbone breakage; for the nitrogenous base pairs, A-T is 30% more sensitive or vulnerable to ion irradiation than G-C, demonstrating a preferential, instead of random, effect of irradiation-induced mutation. © 2010 Elsevier B.V. All rights reserved.